2015
DOI: 10.2215/cjn.09911014
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Enhanced Risk Prediction for Adverse Outcomes in Critically Ill Patients Receiving RRT

Abstract: Background and objectives Higher plasma concentrations of inflammatory and apoptosis markers in critically ill patients receiving RRT are associated with RRT dependence and death. This study objective was to examine whether plasma inflammatory ; macrophage migration inhibitory factor) and apoptosis (death receptor-5, tumor necrosis factor receptor I and II) biomarkers augment risk prediction of renal recovery and mortality compared with clinical models.Design, setting, participants, & measurements The Biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…A recent study by Bajwa et al [73] has also shown that bone marrow-derived dendritic cells deficient in sphingosine 1-phosphate receptor 3 can prevent ischemia-repufusion-induced AKI via a spleen-dependent mechanism and splenic T-regulatory cell expansion. These experimental results are in line with a recent clinical study showing inflammatory cytokine (IL-8), which augments the prediction of kidney recovery and mortality in AKI patients on renal replacement therapy [74] .…”
Section: Immune Responsesupporting
confidence: 86%
“…A recent study by Bajwa et al [73] has also shown that bone marrow-derived dendritic cells deficient in sphingosine 1-phosphate receptor 3 can prevent ischemia-repufusion-induced AKI via a spleen-dependent mechanism and splenic T-regulatory cell expansion. These experimental results are in line with a recent clinical study showing inflammatory cytokine (IL-8), which augments the prediction of kidney recovery and mortality in AKI patients on renal replacement therapy [74] .…”
Section: Immune Responsesupporting
confidence: 86%
“…Pike et al showed that combining plasma IL-8 with a 4-variable clinical model consisting of age, mean arterial blood pressure, mechanical ventilation, and bilirubin value enhanced the prediction of recovery of kidney function and death compared with the clinical model alone [169]. Likewise, the addition of a positive furosemide stress test to an elevation of NGAL > 150 ng/mL or [TIMP-2] × [IGFBP7] > 0.3 improved the predictive ability for AKI progression, need for RRT, and death compared with either biomarker alone [170].…”
Section: Biomarkers Of Aki Outcome Prognosticationmentioning
confidence: 99%
“…These factors were requirement for mechanical ventilation, increasing age, increasing levels of bilirubin, and lower mean arterial pressure. 58 Thus, respiratory complications are a key marker of mortality risk in patients with AKI, suggesting a unique association between AKI and respiratory complications. This paradigm is especially true as the overall mortality of ALI is <20%, 59 whereas the overall mortality of AKI requiring RRT in the ATN trial was >60%.…”
Section: Respiratory Complications In Akimentioning
confidence: 99%
“…SIRS is characterized by the early production and release of proinflammatory cytokines in response to sepsis, pancreatitis, and other systemic (indirect) causes of ALI. Data from patients with AKI indicate that AKI is also associated with a SIRS response and that serum levels of the proinflammatory cytokines IL-6, 47,75-78 IL-8, 47,58,75,78,79 and TNF 75 are increased. Studies suggest that proinflammatory cytokines can induce lung injury by directly injuring the lung endothelium and causing non-cardiogenic pulmonary oedema.…”
Section: Respiratory Complications In Akimentioning
confidence: 99%
See 1 more Smart Citation